2015
DOI: 10.1016/j.neuropsychologia.2015.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Multiple modes of clearing one's mind of current thoughts: Overlapping and distinct neural systems

Abstract: This study used the power of neuroimaging to identify the neural systems that remove information from working memory, a thorny issue to examine because it is difficult to confirm that individuals have actually modified their thoughts. To overcome this problem, brain activation as measured via fMRI was assessed when individuals had to clear their mind of all thought (global clear), clear their mind of a particular thought (targeted clear), or replace the current thought (replace), relative to maintaining an ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…This fits with findings underlining the particular importance of the FPC (BA10) for working memory processes (e.g. 33 34 ).…”
Section: Discussionsupporting
confidence: 90%
“…This fits with findings underlining the particular importance of the FPC (BA10) for working memory processes (e.g. 33 34 ).…”
Section: Discussionsupporting
confidence: 90%
“…One possibility is the involvement of an active cognitive control mechanism, which specifically attempts to dissociate prospectively relevant from currently relevant representations in order to prevent task interference. Such control mechanisms might be exerted through feedback connections emanating from frontal areas central to counteracting unwanted or task-irrelevant information ( Anderson et al, 2004 ; Banich et al, 2015 ; de Vries et al, 2018 ; Depue et al, 2007 ; Reeder et al, 2017 ). Interestingly, an earlier study of memory retrieval has shown suppression of voxel patterns in ventral object-related cortex which were associated with task-irrelevant memories of learned object pictures, leading to comparable patterns of representational dissimilarity as here ( Wimber et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This account suggests intriguing links across several disparate areas of psychology, viz. attention, working memory, surprise, response inhibition, and distractibility (Banich, Mackiewicz Seghete, Depue, & Burgess, 2015;Horstmann, 2006;Leiva, Parmentier, Elchlepp, & Verbruggen, 2015). Here we set out to more thoroughly substantiate the behavioral effect.…”
Section: Introductionmentioning
confidence: 95%